Perekonomian Indonesia Pasca Invasi Amerika ke Irak - - Supriyanto (Universitas Negeri Yogyakarta, 2004)
In order to understand economic of a nation in the increasing of interdependency era, domestic economic and non economic factors identification is insufficient. We must relate them to the abroad economic and non economic phenomena. Non economic factors consist of social, politic, law and foreign affair. Among of the economic factors are economic growth, inflation, exchange rate, foreign reserve, current account and investment. Strong structure and economic fundamental are important to reduce effects of both economic and non economic fluctuation occurring overseas.